COPING MECHANISMS DECREASE ANXIETY LEVELS OF PREGNANT WOMEN DURING THE COVID-19 PANDEMIC IN SOUTH KALIMANTAN - Agustine Ramie; Mahdalena Mahdalena (Proceeding B-ICON, 2022)
Background: The Coronavirus outbreak (Covid-19) has taken the world by storm up to this day, and the effect is experienced around the world, including Indonesia. The current condition is especially risky for pregnant women due to various hormonal changes during pregnancy. Further, the pandemic situation creates anxiety that might result in negative effects on their pregnancies. This study aims to analyses the knowledge of Covid-19 and coping mechanisms for decrease the anxiety level of pregnant women during Covid-19. Method: This study utilizes an observational design with a cross-sectional approach. 324 women with normal pregnancies residing in Banjarbaru city and Banjar district are involved as a sample in this study. This sample is taken through consecutive sampling. Result: The study has found that 48,1% of pregnant women have moderate anxiety level. Among those numbers 85,2% exhibit adaptive coping mechanisms. Further, the data has shown that 44,4% of them exhibit sufficient knowledge of Covid-19. Therefore, it is indicated that a sufficient level of knowledge can help improve pregnant women’s actions in protecting themselves from the possibility of being infected by Covid-19. A good level of knowledge creates an adaptive coping mechanism, and the result is a decrease in anxiety for pregnant women during the Covid-19 pandemic. Conclusion: Sufficient knowledge of Covid-19 results in adaptive coping mechanism exhibition and brings about the decline of anxiety level of pregnant women during the Covid-19 pandemic. It is advisable for a medical practitioner in public health services to identify anxiety levels and provide appropriate information, so that pregnant women can have adaptive coping mechanisms during Covid-19.